Dementia in 'super-aged' Japan: challenges and solutions. (August 2018) - Leroi, Iracema; Kitagawa, Keiko; Vatter, Sabina; Sugihara, Taro
Japan, as a 'super-aged' society, is at the forefront of the socioeconomic change resulting from the unprecedented demographic shift of aging societies, and is an exemplar for other countries. Within neurodegenerative disorders, a deeper understanding of the issues faced by aging societies, and their ramifications on the mental well being and cognitive health of older adults, is important. Japan's pioneering approaches in assistive technology and 'gerontotechnology' have the potential to enhance the field of dementia in terms of assessment, diagnosis and care. This article is a narrative review of the issue of aging and dementia in Japan by discussing demographics, implications of a 'super-aged' society, challenges and potential solutions to the growing issue of dementia in the world's most aged nation.